Relationship between Emotion Regulation and Self-Confidence of Female Hockey Athletes - Dea Destian; Komarudin; Mochamad Yamin Saputra; Geraldi Novian (Universitas Negeri Semarang, 2025)
In the sport of hockey, athletes' ability to regulate emotions is crucial, especially in high-pressure situations. Athletes often face emotional challenges that can affect their self-confidence, such as making mistakes during a game or competing against strong opponents. Poor emotional regulation can lead to a decline in performance, including impaired decision-making, loss of focus, and reduced motivation. This study aims to examine the relationship between emotional regulation and self-confidence in female hockey athletes. A descriptive method with a quantitative approach was used in this study, involving 30 female hockey athletes from various clubs in Jakarta. The instruments used were an emotional regulation questionnaire and a self-confidence scale, which were distributed once to the participants. Data were analyzed using the correlation test with SPSS version 29. The results showed a significant relationship between emotional regulation and self-confidence among female hockey athletes. The correlation value between the variables was 42%, indicating a strong relationship. This study concludes that emotional regulation plays an important role in enhancing the self-confidence of female hockey athletes. Coaches and team managers are encouraged to pay more attention to emotional regulation by providing mental training programs and activities that support emotional well-being.